2009
DOI: 10.1080/02642060802253850
|View full text |Cite
|
Sign up to set email alerts
|

On the identification of critical mass in Internet-based services subject to network effects

Abstract: In many Internet-based services, network effects have a significant impact on the evolution of the market. In particular, critical mass is a fundamental element due to its relevance to the growth process of these kinds of services. The objective of this paper is to set out some of the difficulties concerning the identification of critical mass. According to more conventional approaches, the critical mass is defined by the product's demand curve and its price. However, as shown in this paper, it is not possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…The Korean group uses Web 2.0 services mainly for social networking, whereas the US group uses them more for conducting their tasks. The Spanish group exhibits balanced and high-level usage of both social networking tool and task support tool (Arroyo- Barrigüete et al, 2010;Bendle & Patterson, 2010;Brás et al, 2010;Hsueh et al, 2010;Pechlaner & Bachinger, 2010;Scott & Laws, 2010). The results of this study suggest that global firm should consider the unique behaviour of Web 2.0 users when they develop strategies to leverage Web 2.0 services.…”
Section: The Content Of the Special Issuementioning
confidence: 70%
“…The Korean group uses Web 2.0 services mainly for social networking, whereas the US group uses them more for conducting their tasks. The Spanish group exhibits balanced and high-level usage of both social networking tool and task support tool (Arroyo- Barrigüete et al, 2010;Bendle & Patterson, 2010;Brás et al, 2010;Hsueh et al, 2010;Pechlaner & Bachinger, 2010;Scott & Laws, 2010). The results of this study suggest that global firm should consider the unique behaviour of Web 2.0 users when they develop strategies to leverage Web 2.0 services.…”
Section: The Content Of the Special Issuementioning
confidence: 70%
“…The electronic commerce (e-commerce hereafter) literature has examined e-commerce to create new platforms for a competitive strategy (Celuch et al, 2007;Chang and Wang, 2011) with different advantages associated with adding the internet to the existing channel structure. These advantages include creating a better communication environment, providing more information to meet customer expectations, and support for the continuous development of a firm (Earl, 2000;Harrison et al, 2006;Canavan and Henchion, 2007;Simmons, 2008;Arroyo-Barrigüete et al, 2010). Venkatesan et al (2007) and Hsiao et al (2012) also found multichannel users to be significantly more profitable than single-channel users because multichannel users are active shoppers, purchase larger quantities, and spend more money.…”
Section: Introductionmentioning
confidence: 92%
“…According to the proposed framework, (a) competitive performance depends on strategic alliances, but (b) the size of the impact of alliances depends on the role of knowledge-rich capabilities that are associated with alliancing (Arroyo- Barrigüete, Ernst, López-Sánchez, & Orero-Giménez, 2010;Brás, Costa, & Buhalis, 2010;Cockburn & Henderson, 1998;Duysters & Heimeriks, 2002;George, Zahra, Wheatley, & Khan, 2001). So, the role of the alliance management capability is that of a moderator.…”
Section: Research Contributionmentioning
confidence: 97%